Increasing Environmental Conservation and Economic Value of Waste Through Waste Bank Management - Sabela, Ikne; Adhaeni, Winda; Azzah, Aslikhatul Isti; Ngazizah, Nur (Program Studi Tadris IPA, Fakultas Tarbiyah (IAIN) Kediri, Indonesia, 2022)
The Trirejo Village Government, Loano District, Purworejo Regency has succeeded in educating its people to be aware of a clean and healthy environment. The mindset of the community needs to be changed that waste will be of economic value to improve welfare. One way to maintain a clean environment is the management of a waste bank that can be used as an economic value. The purpose of this activity is to increase environmental conservation and the economic value of waste through waste bank management. The community-based 3R (reduce, reuse, and recycle) waste management strategy is able to change the imagination of many people towards waste that has no economic value. The type of research used is descriptive qualitative. The method used in this research is the phenomenological method as a medium to examine and analyze life. individual in the form of experience of phenomena or appearances as they are which is commonly referred to as consciousness. The TPST 3R waste bank manages waste originating from household waste and other types of household waste. then the waste is also distinguished again between organic and inorganic waste.